The effect of light stimulation technology training on brain signals, motor response time, and jump shot accuracy among young basketball players - Zainab Mizher Khalaf (Universidad de Murcia, 2023)
The purpose of this study was to develop exercises utilizing optical stimulation technology (ST) and determine their impact on some brain signals (EEG), the time of motor responses, and the precision of jumping shots among young basketball players (YBP). By creating one experimental group with a sample of twelve players from the participating clubs in Baghdad, the experimental approach was used. They were chosen at random from their home community with a percentage of 16.6% for the 2020-2021 athletic season. The researcher used lights with a thickness of 0.5 cm that are powered by daytime LED technologies. They run on electricity, and the remote controls them from a distance. They were distributed in the basketball scoring area on the board at specific times. The wires were safely connected, and they did not obstruct the balls path in any way. They were put in place on the field to speed up response times. As a result, the exercises used vision to stimulate the brain. These exercises were performed to their maximum potential using high-intensity interval training, which was carried out for eight weeks in a row, averaging three units per training week, and whose intensity ranged between 85% to 95% of the motor response time (MRT). In conclusion, light ST exercises have a positive role in improving the level of low, medium, and high brain (beta) frequencies, which helps to activate brain work in the motor side of YBP and helps them to improve MRT and the accuracy of shooting from the perimeter.